Influence of the North Atlantic Oscillation (NAO) on the climatic variability and groundwater resources in carbonate aquifers of southern Italy - De Vita, Pantaleone; Fabbroncino, Silvia (Sapienza Università Editrice, 2007)
The analysis of precipitation and air temperature time series, recorded by the monitoring network of the ex-Hydrographic and Tidal National Service (Compartment of Naples) in the period 1921-1999, was carried out in order to assess the temporal evolution of climatic characteristics in Southern Italy. To this end, the mean normalised of annual precipitations gathered by 18 rain gauge stations, selected on the basis of the continuity of their records has been mainly analysed. Results exibit a complex decadal periodicity superimposed to a general decreasing trend. Such observation has been correlated to the North Atlantic Oscillation (NAO), a large scale atmospheric phenomenon influencing the circulation of humid air masses coming into the Mediterranean area from the Atlantic Ocean. The NAO induces annual variations of the barometric gradient between Azores’s high and Iceland’s low. Among the principal results is the correlation between natural fluctuations of the precipitations in Southern Italy and the NAO, similar to what observed in other Mediterranean areas. The aquifer recharge decadal variability has been also analysed in a sample basin corresponding to the Monte Cervialto carbonate hydrogeological unit. The sample aquifer is particularly representative both for the discharge time series duration of the spring Sanità in Caposele (AV), comparable with those of the precipitation ones, and for the relevance of this spring for an important regional aqueduct system. A clear relationship between the decadal variability of the acquifer recharge and the NAO has been demonstrated both respect to the spring discharges and, on the regional scale, respect to the effective precipitations. This result, even if it has to be verified in other type of aquifers, appears original because it demonstrates the influence on the aquifer recharge of a large scale atmospheric phenomenon, well-known in the meteorological and oceanographic scientific framework. It allows further understandings about the relation- ships existing between ...